Hypocholesterolemic Effects of Cold and Hot-pressed linseed oil in A Wistar Rat Model - Aloufi, Bandar H. (Asian Journal of Biological and Life Sciences, 2017)
Hypercholesterolemia is metabolic deregulation of cholesterol levels in the blood and the major risk factor that precipitate coronary heart disease and atherosclerosis.This study aimed to compare the efficiency of cold and hot-pressed linseed oil to decrease the levels of total cholesterol and proteins in Wister rats (n =60) weighing (225-252 g). Linseed oil was fed for seven weeks to Wister rats and control. Many biochemical and physiological parameters were measured by automatic analyzer and the results were statistically analyzed by SPSS.12. In comparison to control rats showed highly significant decrease in values of following physiological parameters; triglycerides, total cholesterol , low density lipoprotein cholesterol, total protein. In contrast, marked increasing in the value of high density lipoprotein cholesterol. Highly significant decrease in rats fed with cold pressed linseed oil blood measurements of triglycerides, total cholesterol, and low density lipoprotein cholesterol. In contrast, marked increasing in the value of high density lipoprotein cholesterol when compared with rats fed with hot pressed linseed oil.These findings indicate that diets containing Linseed oil significantly improved the physiological parameters of rats. We suggest that Linseed oil as part of food might improve blood parameters and increase high density lipoprotein cholesterol in rats. We further suggest that Linseed oil supplementation act as antioxidant agents, and an excellent adjuvant therapy for rats
Keywords: cholesterol; Linseed oil; on lipid Metabolism